Double‐effect of highly concentrated acetonitrile‐based electrolyte in organic lithium‐ion battery. Issue 5 (1st August 2021) - Zhang, Weisheng; Sun, Huimin; Hu, Pandeng; Huang, Weiwei; Zhang, Qichun
Abstract: Organic electrode materials have become a hot research field in lithium‐ion batteries. However, the dissolution issue of organic materials (especially small molecules) in traditional electrolytes has become one of the important reasons to limit their application. The usage of highly concentrated electrolyte (HCE, >3 M) has been demonstrated to solve this problem, where the electrochemical performance of Pillar[5]quinone (P5Q) in 4.2 M LiTFSA/AN electrolyte was investigated. The HCE can avoid the reaction between acetonitrile molecules and lithium metal anode, reduce the dissolution of organic materials, and display excellent battery performance. At a current density of 0.2 C, a high specific capacity of 310 mAh g −1 (C theo = 446 mAh g −1 ) was maintained after 900 cycles, and the reversible capacity is higher than 113 mAh g −1 even at 10 C, indicating a good rate capability. This research would expand the new application of acetonitrile‐based electrolyte in organic secondary battery. Abstract : In this work, a dual‐function acetonitrile‐based electrolyte was reported for organic electrode materials, which effectively alleviating the dissolution of organic materials while avoiding the reaction between free acetonitrile and lithium. This research improved the lithium storage performance of Pillar[5]quinone (P5Q) and promoted the development of organic secondary batteries.